2017
DOI: 10.1126/sciadv.1600663
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic hydrophobic core orchestrates allostery in protein kinases

Abstract: The synchronized motions of inner core residues allosterically modulate the activity of the protein kinase A catalytic subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(161 citation statements)
references
References 55 publications
10
134
0
Order By: Relevance
“…These studies showed the importance of the hydrophobic core in distinct allosteric responses. A more recent study of protein kinase A also demonstrated the importance of the hydrophobic protein core in allostery [38]. The hydrophobic core of PTP1B exhibits species conservation among PTP1B enzymes; however, many of the hydrophobic residues identified in our work as part of the allosteric network are not conserved among human tyrosine-specific phosphatases [22].…”
Section: Resultsmentioning
confidence: 71%
“…These studies showed the importance of the hydrophobic core in distinct allosteric responses. A more recent study of protein kinase A also demonstrated the importance of the hydrophobic protein core in allostery [38]. The hydrophobic core of PTP1B exhibits species conservation among PTP1B enzymes; however, many of the hydrophobic residues identified in our work as part of the allosteric network are not conserved among human tyrosine-specific phosphatases [22].…”
Section: Resultsmentioning
confidence: 71%
“…This method provided atomic‐level insight into how distal amino acid substitutions, like G121V and S148A, can propagate their effects throughout the enzyme. Similar types of network analyses have contributed to our understanding in many other enzyme systems …”
Section: Enzymes As Amino Acid Interaction Networkmentioning
confidence: 88%
“…Similar types of network analyses have contributed to our understanding in many other enzyme systems. [101][102][103][104][105][106][107] These long-range networks may also offer means through which enzymes communicate in multi-enzyme complexes. 97 For example, we used NMR chemical shift covariance analysis 108,109 among a series of sitedirected protein variants to identify amino acid interaction networks in the alpha subunit of E. coli tryptophan synthase (aTS).…”
Section: Enzymes As Amino Acid Interaction Networkmentioning
confidence: 99%
“…One may then speculate that these charged residues, which are perturbed by binding, trigger redistribution of the internal electrostatic interaction energy and thus play a role in CAP allosteric function. Protein kinases were also proposed to be dynamics-driven allosteric proteins (16), where allostery is orchestrated by a dynamic hydrophobic core (17). Like the butterfly effect, a single mutation in cancer can remodel the whole cell (18).…”
mentioning
confidence: 99%